A numerical study of non-Newtonian transient elastohydrodynamic lubrication of metal-on-metal hip prostheses. (January 2016) - Gao, Leiming; Dowson, Duncan; Hewson, Robert W.
Abstract: This paper presents a comprehensive numerical study of transient non-Newtonian elastohydrodynamic lubrication of metal-on-metal hip prosthesis subjected to two different gait cycles. The shear-thinning property of the synovial fluid was found to have a significant effect on the lubricating film, in terms of both the magnitude and location of the minimum film thickness, and more generally the film thickness distribution. A range of clearances between the acetabular cup and femoral head was investigated and the shear-thinning effect was more pronounced in the hip replacements with smaller clearances. Highlights: The shear-thinning property of the synovial fluid affected the lubricating film. Both the magnitude and location of the minimum film thickness were affected. The calculated film thicknesses were increased due to the shear-thinning property. The minimum film thickness increase substantially as the clearance decreases.